Usefulness of Bispectral Index Monitoring for the Detection and Diagnosis of the Brain Death - Kutlay Aydın; Yasin Levent Uğur; Taner Çalışkan; Begüm Ergan; Tuğçe Mengi; Yusuf Savran; Erdem Yaka; Bilgin Cömert; Uğur Koca; Pembe Keskinoğlu; Ali Necati Gökmen (Türk Yoğun Bakim Derneği Dergisi, 2023)

(untitled)
Objective:Bispectral index (BIS) is a parameter generated from a mathematical analysis of frontal cortex activity. BIS monitoring has been widely used in cerebral pathologies such as traumatic brain injury, brain death, metabolic coma and barbiturate coma and some studies have reported a good correlation between neurological status and BIS values. We evaluated the validity of BIS monitoring for the detection and diagnosis of brain death in our studyMaterials and Methods:Our study was a methodological prospective study. Twenty-eight patients with severe coma [Glasgow coma scale score (GCS)<8] at intensive care unit (ICU) admission are monitored by BIS. Eight patients were excluded from the study due to varies reasons. Data of twenty patients with brain death were evaluated.Results:The most common diagnoses were intracranial hemorrhage (8 patients-40%) and subarachnoid hemorrhage (8 patients-40%). The most common used ancillary method was computed tomography angiography. BIS and suppression ratio (SR) were determined as 0 and 100 respectively at the moment of brain death diagnosis in 12 of 20 patients, whereas BIS was determined >0 in the remainders. When the receiver operating characteristic curve analysis was performed for the 34041 BIS values of 20 patients, the area under curve was found as 0.582 (0.576-0.588), which was statistically significant (p<0.05). There was a strong negative correlation between BIS and SR and it was statistically significant (R:-0.959, p<0.05).Conclusion:BIS is a non-invasive method and it may be used in the ICU. BIS monitoring may be useful, especially in patients with head trauma and GCS =3. BIS monitoring provides information about the neurological prognosis. We consider that BIS monitoring can prevent the loss of time by providing to detect the moment of the brain death and thus facilitating the organ transplantation process and however it can not take the place of the other ancillary methods.